فاعلية تقويم الاقران في التحصيل الدراسي لدى تلاميذ المرحلة الثانوية - مهرية، نادية, باي، نريمال (جامعة الوادي university of Eloued, 2020)
Résumé :فرنسية أو انجلزية For this reason, this study indicates the effectiveness of peer evaluation on academic achievement for secondary school students in the experimental sciences from Bannu 2 Accordingly, the study took place in two aspects, the first was theoretical, through volunteering to study variables and secondly, a field aspect in which we used a quasi-experimental approach suitable for this study, where the experiment was a comparison between two sections, each section includes 30 pupils, and equivalence between the two groups was taken into account in academic achievement . Choosing by lot to determine which is experimental and which is a control and we applied the peer evaluation strategy to the experimental group for a set of lessons and the self-evaluation of the control group, then we conducted an achievement test designed by the teacher of the article on the lessons provided. After statistical treatment, we get the following results: There are related differences in statistical evidence between two groups, and this confirms the existence of the effectiveness of peer evaluation in academic achievement.
دراسة ميدانية بثانوية عبد الرزاق عيده بالوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: التقويم التربوي، التحصيل الدراسي; calendrier éducatif, réussite scolaire; Educational evaluation, academic achievement